Practical Nephrology - Harber, Mark (Springer London, 2014)
This book will provide readers with a practice-based approach to all aspects of clinical nephrology. Written by experts in the field, Practical Nephrology offers invaluable practical advice on how to manage specific illnesses and, uniquely, the importance of establishing systems and processes to improve patient safety, enhance the patient pathway and guidance on how to systematically improve clinical governance. A unique aspect of this book are the tips and tricks and, suggestions for avoiding common errors based on the vast experience of the authors. In addition, the Editor has collated a list of links to international registries and guidelines as well as selected disease specific organisations, providing both clinicians and patients with access to helpful and recommended resources. Designed and written in a user-friendly fashion, Practical Nephrology will be the definitive reference for practising nephrologists, trainees and non-nephrologist who encounter renal patients in their daily practice.